Controller design of a tidal system - Nur Insyirah Sazali (Nanyang Technological University, 2022)
The increased use of fossil fuels over time to meet consumer needs has had a considerable impact on the overall climate change. Renewable energy sources, such as tidal turbines, are being deployed to help alleviate the impact. The purpose of this research is to conduct a literature evaluation of the tidal turbine system in order to obtain a better understanding of tidal energy in general and its numerous technologies.